2023
DOI: 10.1590/1519-6984.249424
|View full text |Cite
|
Sign up to set email alerts
|

Stoichioproteomics study of differentially expressed proteins and pathways in head and neck cancer

Abstract: Hypoxia is a prominent feature of head and neck cancer. However, the oxygen element characteristics of proteins and how they adapt to hypoxia microenvironments of head and neck cancer are still unknown. Human genome sequences and proteins expressed data of head and neck cancer were retrieved from pathology atlas of Human Protein Atlas project. Then compared the oxygen and carbon element contents between proteomes of head and neck cancer and normal oral mucosa-squamous epithelial cells, genome locations, pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…The latest research suggests that ligustilide may inhibit the activation and apoptosis of cancer-associated fibroblasts (CAFs) in the tumor microenvironment, thereby altering the immunosuppressive function of CAFs ( 20 ). In addition, no research to date has suggested that ligustilide had anti-cancer effects in oral cancer cells, but it is known that a hypoxic microenvironment is a significant feature of oral cancer ( 21 ). Therefore, this study aims to explore the anti-cancer activity and related molecular mechanisms of ligustilide on hypoxic oral cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The latest research suggests that ligustilide may inhibit the activation and apoptosis of cancer-associated fibroblasts (CAFs) in the tumor microenvironment, thereby altering the immunosuppressive function of CAFs ( 20 ). In addition, no research to date has suggested that ligustilide had anti-cancer effects in oral cancer cells, but it is known that a hypoxic microenvironment is a significant feature of oral cancer ( 21 ). Therefore, this study aims to explore the anti-cancer activity and related molecular mechanisms of ligustilide on hypoxic oral cancer cells.…”
Section: Introductionmentioning
confidence: 99%